ANALISIS KEMAMPUAN PEMECAHAN MASALAH MATEMATIS SISWA KELAS XI PH 4 SMKN 6 SEMARANG PADA MATERI MATRIKS BERDASARKAN LANGKAH POLYA - Eva Nabila Zulfaniar; Rasiman; Pramono (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2024)
The purpose of this research is to analyze how students' mathematical problem solving skill are in solving problem problems in matrix material. This research method is in the form of a descriptive method using a qualitative approach. The subjects of this research were students of class XI PH 4 SMKN 6 Semarang with a total of 35 students. The instrument used is a test instrument in the form of 4 questions describing the matrix material, and each question refers to an indicator. The results of the research show that students' mathematical problem solving abilities are in the high category, was 6 students or (17.14%), then as many as 24 students or (68.57%) were catagorized as medium, and as many as 7 students or (20%) were catagorized as low. From this research it has been obtained that students' problem solving abilities are based on the polya stages, namely at the stage of understanding the problem, preparing a solution plan, carrying out the solution plan, re-examining and making conclusions, there are still students who do not carry out the process of understanding the problem, then develop a problem plan that is lacking. correct, not solving the problem given, and students not checking again and drawing conclusions is not correct. Students' mathematical problem solving abilities are still in the medium category, students are expected to continue learning and practicing so that students are more accustomed to solving problems with problem solving skills.